Bounding the number of segment histories during data race detection - Christiaens, Mark; Ronsse, Michiel; De Bosschere, Koen (Parallel computing, 2002)
In this article we present a technique for reducing the memory overhead while performing data race detection. Data races occur when multiple threads modify the same memory location without proper synchronization. In order to detect data races, we need to check all read and write operations performed by the threads. We describe a method for efficiently storing these read and write operations called “merging of segment histories”. This method improves upon known techniques by ensuring an upper limit to the amount of memory consumed for storing the read and write operations while maintaining the full accuracy of the data race detection. The method has been implemented in an existing data race detection tool called RecPlay for Solaris binaries. We show that it enables us to perform data race detection on benchmarks which were previously beyond our grasp.